Ultra-processed people : the science behind food that isn't food - Tulleken, Chris van, 1978- (W.W. Norton & Company, 2023)
"We have entered a new age of eating. For the first time in human history, most of our calories come from an entirely novel set of substances called Ultra-Processed Food. There's a long, formal scientific definition, but it can be boiled down to this: if it's wrapped in plastic and has at least one ingredient that you wouldn't find in your kitchen, it's UPF. In this book, Chris van Tulleken, father, scientist, doctor, and award-winning BBC broadcaster, marshals the latest evidence to show how governments, scientists, and doctors have allowed transnational food companies to create a pandemic of diet-related disease. The solutions don't lie in willpower, personal responsibility, or exercise. You'll find no diet plan in this book--but join Chris as he undertakes a powerful self-experiment that made headlines around the world: under the supervision of colleagues at University College London he spent a month eating a diet of 80 percent UPF, typical for many children and adults in the United States. While his body became the subject of scientific scrutiny, he spoke to the world's leading experts from academia, agriculture, and--most important--the food industry itself"--